Responses of Angiogenic Growth Factors to Exercise, to Hypoxia and to Exercise under Hypoxic Conditions - Wahl, P.; Schmidt, A.; deMarees, M.; Achtzehn, S.; Bloch, W.; Mester, J. (International Journal of Sports Medicine, 2013)
The purpose of the present study was to compare the acute hormonal response of angiogenic regulators to a short-term hypoxic exposure at different altitudes with and without exercise. 7 subjects participated in 5 experimental trials. 2 times subjects stayed in a sedentary position for 90 min at 2 000 m or 4 000 m, respectively. The same was carried out again in combination with exercise at the same relative intensity (2 mmol∙L − 1 of lactate). The fifth trial consisted of 90 min exercise at sea level. Venous blood samples were taken under resting conditions, 0 and 180 min after each condition to determine VEGF, EPO, IL-6, IL-8 and IGF-1 serum concentrations. EPO, VEGF, and IL-8 showed increases only, when hypoxia was combined with exercise. IL-6 was increased after exercise, independent of altitude. IGF-1 showed no changes in any intervention. The present study suggests that short term hypoxic exposure combined with low intensity exercise is able to up-regulate angiogenic regulators, which might be beneficial to induce angiogenesis and to improve endurance performance. However, in some cases high altitudes are needed, or it can be speculated that exercise intensity needs to be increased.
Keywords: angiogenesis; VEGF; EPO; IL-6; IL-8; IGF-1